Pengaruh Insentif Pajak dan Cash Flow Terhadap Konservatisme Akuntansi - Yoseb Boari; Emi Yulia Siska; Shofia Yunus Manginte; Diah Hari Suryaningrum; Loso Judijanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of tax intensity and cash flow on accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange. This research is quantitative research using panel balance data collected using documentation techniques obtained via the website www.idx.co.id and the official website of each company which is analyzed using panel data regression using the SPSS analysis tool. The sample in this research was 150 manufacturing companies with a sampling technique using purposive sampling technique. The results of research using partial tests show that tax intensification has a negative and significant effect on accounting conservatism, cash flow has a positive and significant effect on accounting conservatism.